2018
DOI: 10.1007/s11356-018-3084-x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne foliar transfer of particular metals in Lactuca sativa L.: translocation, phytotoxicity, and bioaccessibility

Abstract: The uptake, translocation, and human bioaccessibility of metals originating from atmospheric fine particulate matters (PM) after foliar exposure is not well understood. Lettuce (Lactuca sativa L.) plants were exposed to micronic PbO, CuO, and CdO particulate matters (PMs) by the foliar pathway and mature plants (6 weeks old) were analyzed in terms of: (1) metal accumulation and localization on plant leaf surface, and metal translocation factor (TF) and global enrichment factor (GEF) in the plants; (2) shoot gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…According to Sgrigna et al [35], the enhanced air turbulence around the leaves that resulted from a higher leaf area index causes the increase in the dry deposition of contaminated particulate matters. In turn, Xiong et al [10] showed that the metal-enriched particles firstly adhere to the leaf surface as aggregates, and they are then partly trapped by the epicuticular waxes and partly penetrate in the leaf tissue through stomata. Subsequently, Pb, Cd, and Cu ions from directly exposed leaves are transferred to the newly formed leaves and roots.…”
Section: Harmful Effects Of Tes and Their Consequence On Plant Orgmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sgrigna et al [35], the enhanced air turbulence around the leaves that resulted from a higher leaf area index causes the increase in the dry deposition of contaminated particulate matters. In turn, Xiong et al [10] showed that the metal-enriched particles firstly adhere to the leaf surface as aggregates, and they are then partly trapped by the epicuticular waxes and partly penetrate in the leaf tissue through stomata. Subsequently, Pb, Cd, and Cu ions from directly exposed leaves are transferred to the newly formed leaves and roots.…”
Section: Harmful Effects Of Tes and Their Consequence On Plant Orgmentioning
confidence: 99%
“…The reduced root-to-shoot transport results from: (1) the presence of Casparian strips in the endodermis, which play a role of physical barrier regulating water and ions movement to the stele, (2) precipitation in the intercellular space as insoluble metal-salts, or sequestration in the vacuoles of cortex cells [40,41,42]. Similarly, after foliar deposition, a majority of the TEs remain in the organ by which they are absorbed and only less than 1% of ions is transported to root tissues and other organs [10,43]. However, the mechanisms preventing the translocation of leaf-absorbed TEs within the organism still remain unknown.…”
Section: Harmful Effects Of Tes and Their Consequence On Plant Orgmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of heavy metals on plants are multifaceted, mainly including plant growth, plant dry weight, net photosynthesis, stomatal conductance, etc. [27]. Such studies are important for analyzing plant mechanisms of physiological and ecological adaptation after short-term exposure to Pb and Cd.…”
Section: Introductionmentioning
confidence: 99%
“…During stress, plants suppress some life functions because their stress-signalling networks need energy for survive; one of these functions is the photosynthetic capacity. The increase in biomass depends on the quantity of bound carbon dioxide during photosynthesis [42,43]. Molecular biological studies demonstrated downregulation of photosynthetic gene expression by abiotic stress, and consequently, this regulation also decreases plant growth [44] We demonstrated that PAHs could reduce the biomass and the decrease in biomass was significantly higher with increasing the number of treatments; after the fourth treatment, the biomass compared to the control was 63.63%.…”
Section: Discussionmentioning
confidence: 87%